Treatment of urticaria: a clinical and mechanistic approach. Issue 4 (August 2019) - Kaplan, Allen P.
Abstract : Purpose of review: This manuscript describes the recommended therapy of chronic spontaneous urticaria based on our understanding of the pathogenesis of hive formation. Thus, the mechanism of action of each medication is elaborated in addition to a discussion of clinical utility. Recent findings: The main drugs are antihistamines, omalizumab, and cyclosporine with a success rate of 40–55, 65–80, and 70–80%, respectively. Used in sequence, over 90% of patients can be successfully treated. The addition of omalizumab represents a major advance because of its efficacy, easy utility, and favorable side-effect profile. The interaction with IgE eliminates any reaction with antigens to which it might be directed, down regulates IgE receptors on mast cells and basophils, and leads to down-regulation of mast cell functions with amelioration of hives. Summary: The use of antihistamines in high dosage (at least four times a day) is effective in close to half the patients with CSU. For antihistamine resistance, the use of omalizumab has revolutionized therapy of antihistamine-resistant cases because of its efficacy and excellent side-effect profile. If the response is insufficient, cyclosporine is the next choice. Patients should be monitored regarding any adverse effects on blood pressure or renal function. All these are far safer than extended use of corticosteroid.